Facilities management research in Finland – state‐of‐art about current Finnish PhD‐projects. Issue 1 (2014) - ,; ,
Abstract : Purpose – The goal of this paper is to present a description of ongoing PhD‐projects as a part of facilities management (FM) research in Finland.Design/methodology/approach – The empirical evidence is collected from PhD‐research projects, the facilities management research sector in Finland. The aim is to identify and analyze: drivers for the research; dominant research themes; theories; research methods.Findings – The Finnish research in facilities management began already in the beginning of 1990s at Helsinki University of Technology (nowadays Aalto‐University). The research followed the embryonic phase of development of facilities management as a profession. At first the research was focusing on the facility services, e.g. problems related to outsourcing, contracting‐out, co‐operations. Nowadays, the research focus is wider and more scattered as a topic and methods wise.Research limitations/implications – The paper describes the situation only in one Finnish university in Finland excluding the research projects, which do not aim to doctoral degrees.Practical implications – The focus is on research, but the reflections to the development of the industry as well as to the affordance in the education can be made. The results offer material for the future research agenda and also for collaborative and comparative research initiatives.Originality/value – This paper provides important input to the European FM research by describing the current PhD research initiatives in Finland. The overview is useful in the discussion of topics for FM research, relevance and implications for practice, and the development of FM as an academic field.